Principality of Serbia on the road towards European monetary standards - Gnjatović Dragana (Bankarstvo, 2015)
In 1868, after more than four centuries, the Principality of Serbia decided to rebuild national monetary system in line with the minting standards of the Latin Monetary Union. The paper explains the international circumstances in which this decision was made and analyzes a specific plan created for the implementation of monetary reform. Because of the general shortage of small coins in circulation, Serbia decided firstly to mint domestic copper and small silver coins, and subsequently larger denominations of silver and gold coins. The research is based on archival documents of the State Council of the Principality of Serbia that are kept in the Archives of Serbia in Belgrade.